Rezul'taty i perspektivy ispol'zovaniya technologii kvantovoj biofiziki v podgotovke vysokokvalificirovannych sportsmenov - Bundzen, P. V.; Korotkov, K. G.; Makarenko, O. I. (Teorija i Praktika fiziceskoj Kul'tury, 2003)
The new bioelectrographical technology of the functional express-diagnostics of the phychophysical potential of elite athletes, basing on the modern achievements of the quantum biophysics and medicine are presented in this paper. The quantum mechanisms of biopower processes and design features of the hardware-software complex for their studying were considered. The results of complex researches on the approbation of the developed technology for the selection of athletes of an Olympic reserve in the view of their genetypical features, and also the automated rating of the functional preparedness of elite athletes are given.